Simultaneous achievement of high strength and large elongation in extruded Mg/LPSO alloys via the anisotropic mechanical property-induced ductilization (AMID) mechanism - Koji Hagihara; Tsuyoshi Mayama; Michiaki Yamasaki; Toko Tokunaga; Mika Sugita; Soya Nishimoto; Kazuki Yamamoto; Kanato Umemura (Journal of Magnesium and Alloys)
We discovered two distinctive features in the mechanical properties of extruded Mg alloys containing a long-period stacking ordered (LPSO) phase, which are highly desirable for a new class of high-strength, lightweight materials. First, the Mg/LPSO-extruded alloy shows greater elongation compared to other Mg solid-solution-extruded alloys when a certain high strength is required. Second, the simultaneous achievement of high strength and large elongation in the Mg/LPSO-extruded alloy enhances with a reduction in extrusion speed. In this study, the physical origins of these features were examined, focusing on how changes in the microstructure affect the mechanical properties of the extruded alloys. Our findings clarify that the LPSO phase contributes not only to increased strength but also to enhanced elongation through an increase in the work-hardening rate, a mechanism we termed “anisotropic mechanical property-induced ductilization” (AMID). Until now, most efforts to improve the ductility of Mg materials have focused on achieving “isotropic mechanical properties” via grain refinement. Based on our results, we propose an entirely opposite approach: increasing the elongation of Mg alloy by locally enhancing their “anisotropic mechanical properties” through the AMID mechanism. Computational analysis further suggests that reducing the diameter of Mg-worked grains should effectively improving elongation in Mg/LPSO alloys with a high volume fraction of Mg-worked grains.